THE EFFECT OF THE APPLICATION OF GREEN ACCOUNTING ON THE FIRM VALUE WITH FOREIGN OWNERSHIP AS MODERATION - Luayyi, Sri; Oktavia, Nila; Attarie, Prima Noermaning (Proceeding of International Conference on Multidisciplinary Research, 2024)
Firm value is the main consideration when investors want to invest in a company. One of the factors that can increase the value of the company is green accounting. Green accounting is part of the development of the triple bottom line concept where green accounting discusses how accounting can be more friendly between economic and business systems towards society and the environment which are a unified system. All decisions taken to increase the value of the company cannot be separated from the role of shareholders who also provide input and decisions including foreign ownership. The purpose of this study of the study is to analyze the effect of implementing green accounting on firm value with foreign ownership as moderation. The population in this study are energy sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2022. The sampling technique used purposive sampling. The analytical method used is descriptive statistical analysis, classical assumption test, and Moderating Regression Analysis. The results of this study found that green accounting proxied by disclosure of carbon emissions affects firm value and foreign ownership can moderate the effect of green accounting on firm value.